MONITORING OF TRAFFIC USING UNMANNED AERIAL VEHICLE IN MALAYSIA LANDSCAPE PERSPECTIVE (Jurnal Teknologi (Sciences & Engineering), 2015)
Collecting information on traffic flows are important for provide high quality road system. At present, fixed camera is widely used for the monitoring system which covers limited area.Â  Therefore, the unmanned aerial vehicle (UAV) such as quadrotor is developed for monitoring traffic flow since the UAV is responsive mobile sensing system. This development of UAV platform is a starting point for developed a highway traffic and management system which is in future can be enhance by connected the system with graphical user interface (GUI) on ground control station that can defined types of vehicles and analyze level of congestion. At present, the system that developed only transmits a real time video to ground control station without any interpretation by software that detects types of vehicles and analyzes traffic condition. Through the surveillance and monitoring of traffic flows that done at Engineering Campus, Universiti Sains Malaysia, the system provides suitable information for authorities to analyse level of congestion happened on the road and provide alternative solution for users in order to avoid the traffic jam.Â Â